The accurate assessment of small‐angle X‐ray scattering data. (1st January 2015) - Grant, Thomas D.; Luft, Joseph R.; Carter, Lester G.; Matsui, Tsutomu; Weiss, Thomas M.; Martel, Anne; Snell, Edward H.
<x xml:space="preserve">Abstract</x> Small‐angle X‐ray scattering (SAXS) has grown in popularity in recent times with the advent of bright synchrotron X‐ray sources, powerful computational resources and algorithms enabling the calculation of increasingly complex models. However, the lack of standardized data‐quality metrics presents difficulties for the growing user community in accurately assessing the quality of experimental SAXS data. Here, a series of metrics to quantitatively describe SAXS data in an objective manner using statistical evaluations are defined. These metrics are applied to identify the effects of radiation damage, concentration dependence and interparticle interactions on SAXS data from a set of 27 previously described targets for which high‐resolution structures have been determined via X‐ray crystallography or nuclear magnetic resonance (NMR) spectroscopy. The studies show that these metrics are sufficient to characterize SAXS data quality on a small sample set with statistical rigor and sensitivity similar to or better than manual analysis. The development of data‐quality analysis strategies such as these initial efforts is needed to enable the accurate and unbiased assessment of SAXS data quality.